The 100 most cited articles in lateral epicondylitis research: A bibliometric analysis - Zhu, Senbo; He, Zeju; Bi, Qing; Cao, Li; Gu, Haifeng; Zhang, Qiong; Chai, Fang (Frontiers in Surgery, 2023)
Introduction: Lateral epicondylitis is a significant clinical problem in orthopaedics. There have been numerous articles written about this. Bibliometric analysis is critical for determining the most influential study in a given field. We attempt to identify and analyze the top 100 citations in lateral epicondylitis research. Materials and methods: On December 31, 2021, an electronic search was conducted in the Web of Science Core Collection and the Scopus search engine with no restrictions on publication years, language, or study design. We reviewed each article's title and abstract until the top 100 were documented and evaluated in various ways. Results: Between 1979 and 2015, the 100 most cited articles were published in 49 journals. The total number of citations ranged from 75 to 508 (mean±SD, 145.5±90.9), with citation densities ranging from 2.2 to 37.6 citations per year (mean±SD, 8.7±6.5). The United States is the most productive country, and the 2000s witnessed a surge in lateral epicondylitis research. The year of publication had a moderately positive correlation with citation density. Conclusion: Our findings offer readers a fresh perspective on historical development hotspot areas of lateral epicondylitis research. Disease progression, diagnosis, and management have always been topics of discussion in articles. PRP-based biological therapy has emerged as a promising area for future research.